KARAKTERISTIK SENSORIS DAN KIMIA PADA ABON NANGKA MUDA (Artocarpus heterophyllus LMK) DENGAN PENAMBAHAN TEMPE - Ulfa Qurrota A’yuni Nur Jannah; Darimiyya Hidayati; Abdul Aziz Jakfar (AGROINTEK, 2016)
Unripe jackfruit is one vegetables that  is usually processed into Indonesian dishs. Beside unripe jackfruit processed into vegetables can also be developed and processed into a dry product called beef floss. Unripe jackfruit has a very low protein content, so it needs other raw material to improve protein content of the floss we added tempeh to the floss = gembus tempeh or soybean tempeh, as much as 15%, 25%, 35% and 0% as control. This study uses a Completely Randomized Design (CRD) with 2 factors. The first factor is proportion of unripe jackfruit and tempeh, and the second factor is type of tempeh. Parameter of this research are organoleptic evaluation, the color, moisture content and protein content. The result of organoleptic evaluation is the proportion 25% soybean tempeh prefered for aroma, taste, color, texture. The highest L (Lightness) was resulted from 35% soybean tempeh. The highest moisture content was shown by floss with 15% soybean tempeh. Protein content increased from 4,3775% to 39,3975% by addition of soybean tempeh while protein increased from 4,3775%  to 14,8835% in beef floss added with gembus  tempeh.